A face for Picasso : coming of age with Crouzon Syndrome - Henley, Ariel, 1992- (Farrar Straus Giroux, 2021)
The author describes how she and her identical twin sister were born with Crouzon syndrome, a rare condition where the bones in the head fuse together prematurely. Details how she and her sister endured numerous surgeries growing up, and their efforts to appear normal and gain acceptance. The author reflects on how she learned to live with a facial disfigurement and what she discovered about beauty, sisterhood, and courage.